A modelagem matemática e a prevenção do bullying: caminhos para o desenvolvimento sociomoral no espaço escolar em perspectiva interdisciplinar - Lima, Larissa Borges de Souza (2021)
The aim of our research is to analyze how the texts on mathematical modeling were recognized and carried out, focusing on bullying and sociomoral development in a collaborative e-learning space, supported by basic education mathematics teachers. The study was developed based on data from the inter-institutional, financial research project by CNPq, Mathematical modeling in basic education: effects of problematic teaching, involving 47 mathematics teachers from different public schools in the state of Bahia about the cities: Vitória da Conquista, Amargosa and Feira de Santana - that might have some kind of interest in participating in a collaborative training in modeling. According to the documentary analysis of the collected data and various e-learning environments, such as Google Meet, Classroom, Lives, categories of analysis were developed, in a qualitative approach, through the sociological model of the description language proposed by Basil Bernstein. Some theoretical elements allowed us to dialogue about bullying, as a complex phenomenon, and about the articulation of this interdisciplinary theme through mathematical modeling, seeking to identify a formative process that can favor a reflection on bullying and a learning environment that focuses on itself. The existing results show us the existence of different dimensions involved, in an e-learning formative environment, from selection and organization, management, internal recontextualization and, legitimation, of the texts, so that teachers could produce legitimate texts about bullying and modeling to its implication - the way in which there was involvement with the reality installed in its institutions, engage themselves toward to proposal of implementing anti-bullying actions in school documents based on the planned modeling activities.